Removing Dual-Discourse (National and Shari’ah Law) in the Formulation of Region’s Policy in Jember - Muhaimin (Jurnal Hukum Islam, 2021)
This article will explore that irrelevant today to say there are differences between Shari’ah Jurisprudences and secular/modern state formulation of law. Yet, Islam as a major religion in Indonesia had dominant roles to construct regulation based on their beliefs in Islamic teaching. Besides that, Moslem society also could respond to the un-universal law if it is compatible with Islamic values through social and political movements. Therefore, this article also will define what Islamic regulation point of view and embedded beliefs of Moslems written inside the regulation. This article will be conducted by qualitative research model and approached by social-phenomenological perspective. In the end, this article concludes that based on maqashid al shari’ah there are not dichotomies of Islamic regulation or modern/secular law in Indonesia, especially in Jember (the object of study) caused the formulation of this regulation was based on Islamic law process and substantive teleological to become Moslem society in Indonesia.